The results of alcoholic septal ablation in the treatment of hypertrophic cardiomyopathy - B.M. Todurov; G.I. Kovtun; A.V. Khokhlov; O.V. Pantazi; A.O. Shpachuk; A.Yu. Melnik; A.O. Maksakov; A.S. Batsiun (Кардіохірургія та інтервенційна кардіологія)
Hypertrophic obstructive cardiomyopathy іs a relatively common condition and one of the most common causes of sudden cardiac death in young age. One of the options for the surgical treatment of this pathology is septal myoectomy, which has been the gold standard for decades. However, despite this, surgical treatment is intended for young patients with a low risk of postoperative complications, while patients with concomitant diseases and a higher surgical risk require alternative treatment. Today, alcohol septal ablation is considered an effective, minimally invasive method for treating hypertrophic obstructive cardiomyopathy in patients with a left ventricular outflow tract gradient ≥ 50 mm Hg. The article presents the experience of using alcohol septal ablation in 57 patients with obstruction of the left ventricular outflow tract.